REVIEW OF CANCER STATISTICS IN INDIA - Raj, Priya; M, Muthulekshmi (International journal of advances in signal and image sciences, 2015)
This study reports key information's about breast and cervical cancer in India. Among various health-related issues, the maximum mortality is due to cancers of different types. Due to the late diagnosis and treatment in India, 0.3 millions of people died per year and increasingly every year. According to diverse cancers breast and cervix carcinomas are considered as the deadliest carcinoma due to its increased mortality among Indian women. As per cancer statistics in 2012, 4.77 lakh and 5.37 lakh men and women are affected by different types of cancers in India. This review focuses the Indian statistics of breast cancer along with cervical cancer.